TAFSIR MUQARAN IBNU KATSIR DAN AL-MARAGHI Q.S. AL-ISRA’: 1 - Nasokah - (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
Tafsir Muqaran is the interpretation of the Qur'an that compares the interpretation of some verses. Lafadz muqarran comes from the Arabic word: (المقارنة) which means comparison. • The al-muqarran interpretation method that the writer intended here is as known to al-Farmawi as a method of interpretation of the Qur'an by introducing verses of the Qur'an 'written by a number of muqirirs, wherein a mufasir compiled a number of verses of the Qur'an, then writes and examines the interpretation of a number of verses about the verse through their tafsir books. Are they interprets from the generation of salaf or khalaf, whether they are interpreted bi al-matsur, or tafsir bi ra'yi. • • In this case the writer will compare between Ibn Katsir's interpretation and al-Maraghi about Q.S. al-Isra ': 1. From the tafsir method of al-muqarran here the writer wishes to examine and try to make a comparison of the direction and tendency between tafsir ibn katir and maraghi and try to analyze what is their background, so their tendency can be clearly seen whether it is only inclined with the aspects of i'rab and balaghah, stories and events that are irrational without aqli and naqli arguments, or a tendency to one of the schools or they are affected by ideas of natural science or other scientific theories.